2015
DOI: 10.1093/intqhc/mzv084
|View full text |Cite
|
Sign up to set email alerts
|

Documentation and disclosure of adverse events that led to compensated patient injury in a Norwegian university hospital

Abstract: Underreporting and nondisclosure of patient injuries remain a problem, despite a mandatory reporting system. Helping physicians and surgeons recognize adverse events, reporting them and discussing them with patients should be a priority for hospitals and medical schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…However, all these methods give only a partial picture of AE. Reporting systems, operating generally at local level, are strongly dependent on the willingness of staff and local quality culture [16]. Safety indicators based on routinely collected data are promising to allow hospitals to benchmark their performance but most suffer from validity concerns due to medical information inaccuracy or incompleteness and case-mix bias [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…However, all these methods give only a partial picture of AE. Reporting systems, operating generally at local level, are strongly dependent on the willingness of staff and local quality culture [16]. Safety indicators based on routinely collected data are promising to allow hospitals to benchmark their performance but most suffer from validity concerns due to medical information inaccuracy or incompleteness and case-mix bias [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…A standardized reporting and documentation of both adverse events and reactions is essential [35,61,62]. For drug safety, the FDA developed a reporting system in 1998 [63].…”
Section: Discussionmentioning
confidence: 99%
“…We think that both patients' and physicians' reports should be included when evaluating safety aspects of a medical intervention while electronic documentation tools might support this. Patients (or their relatives) can play an important role in signalling safety aspects in clinical trials as well as in routine care [62,69] and can help the patient-centred approach in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, even if Norway has a mandatory reporting system for the most severe adverse events, underreporting in documentation and disclosure of adverse events in hospitals remains a problem. Studies show that only one in four adverse events causing injury or death are reported through incident reporting systems in hospitals (Smeby et al, 2015).…”
Section: Adverse Events In Cancer Treatment In Norwaymentioning
confidence: 99%